2017
DOI: 10.1037/pas0000399
|View full text |Cite
|
Sign up to set email alerts
|

Using the MAYSI-2 to identify mental disorder among Latino juvenile offenders.

Abstract: Many juvenile justice agencies have adopted the Massachusetts Youth Screening Inventory-Version 2 (MAYSI-2; Grisso & Barnum, 2006) to facilitate appropriate programming for young offenders with mental illness. Although Latinos are the fastest-growing ethnic group in the criminal justice system, there is scant research on the utility of the MAYSI-2 among Latino adolescents. The present study examined the utility of the MAYSI-2 in detecting diagnosable mental illness among 398 Latino and 60 European American ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…A licensed clinical psychologist and doctoral-level researcher administered the training program and provided clinical supervision for interviewers. Overall, interviewers in our study demonstrated high interrater reliability (a mean weighted κ = .82); further detail on interviewer qualifications and training is described in Eno Louden et al (2017).…”
Section: Methodsmentioning
confidence: 55%
See 4 more Smart Citations
“…A licensed clinical psychologist and doctoral-level researcher administered the training program and provided clinical supervision for interviewers. Overall, interviewers in our study demonstrated high interrater reliability (a mean weighted κ = .82); further detail on interviewer qualifications and training is described in Eno Louden et al (2017).…”
Section: Methodsmentioning
confidence: 55%
“…The current study investigated the factor structure and convergent validity of the MAYSI-2 among a sample of Latino youth. Although prior research has examined the psychometric properties of the MAYSI-2 among ethnically diverse samples comprised predominantly of African Americans and European Americans (e.g., Archer et al, 2010; Archer et al, 2004; Eno Louden et al, 2017; Ford et al, 2008; Grisso et al, 2001), this study is the first to examine the measure’s factor structure and convergent validity among Latino youth. Overall, our results provide promising evidence for the generalizability of the MAYSI-2 to Latino youth who are involved in the juvenile justice system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations